Kajian Hukum terhadap Notaris melalui Digitalisasi Layanan Hukum - Norman Adrianto; Endang Sutrisno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The digitalization of notarial services is a consequence of the development of information technology that has influenced the provision of legal services in Indonesia. This study aims to analyze the legal regulations for the digitalization of notarial services in the Indonesian legal system and its impact on notaries' responsibilities for the legal risks that arise. The research method used is normative juridical with a statutory and conceptual approach. The results show that the regulation of the digitalization of notarial services is still partial and does not provide legal certainty regarding the implementation of authentic deeds electronically. Digitalization also creates legal risks that have implications for notaries' administrative, civil and criminal responsibilities. Therefore, more comprehensive regulatory updates are needed to ensure legal certainty and protection.